2008
DOI: 10.1097/smj.0b013e318189aa56
|View full text |Cite
|
Sign up to set email alerts
|

Blood B-Type Natriuretic Peptide and Dialysis: Present Assessment and Future Analyses

Abstract: Brain natriuretic peptide (BNP) is elevated in hemodialysis (HD) patients and predicts increased mortality. Intra- and interdialytic changes in BNP have not been fully described. End-stage renal disease (ESRD) patients were prospectively recruited at three dialysis centers. At five visits, over a 6-week period, pre- and postdialysis BNP levels were measured. Pre- and postdialysis weights, blood pressure, fluid removed/given and demographic/medical information were recorded. Mean pre- and post-HD BNP (log-trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
0
5
0
1
Order By: Relevance
“…One out of five men were current smokers (21.0%), while very few women smoked (0.3%). The median number of servings of fruits and vegetables eaten per day was very low (1.86 servings/day, data not shown) compared to the five or more servings recommended by the Ministry of Health, Oman (20).…”
Section: Resultsmentioning
confidence: 84%
“…One out of five men were current smokers (21.0%), while very few women smoked (0.3%). The median number of servings of fruits and vegetables eaten per day was very low (1.86 servings/day, data not shown) compared to the five or more servings recommended by the Ministry of Health, Oman (20).…”
Section: Resultsmentioning
confidence: 84%
“…Understanding the mechanisms that underlie elevation in BNP/NT-proBNP levels among ESRD patients is of particular importance to help frame appropriate therapeutic decisions. Previous studies have suggested that the mechanism for a rise in NPs among ESRD patients was a result of LV structural and functional abnormalities [6] , [41] , enabling NPs to be a potential marker of LV hypertrophy in ESRD [42] , [43] . In addition,there is emerging evidence that increases in circulating NPs may indicate myocardial ischemia or necrosis, due to the coronary atherosclerosis prevalent in patients with ESRD [6] , [44] , supported by a strong relationship between elevated BNP/NT-proBNP and cardiovascular mortality/events in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…BNP/NT-proBNP concentrations have not been shown to correlate with short-term changes in volume state [55],[56]. Their role as volume markers in the medium to long-term remains an important, unresolved issue.…”
Section: B-type Natriuretic Peptidesmentioning
confidence: 99%